Effect of technique and impression material on the vertical misfit of a screw-retained, three-unit implant bridge: An in vitro study - Hamidreza Rajati Haghi; Masoud Shiehzadeh; Mohammadreza Nakhaei; Fatemeh Ahrary; Saeid Sabzevari (Wolters Kluwer Medknow Publications, 2017)
Introduction: A dental impression is a negative imprint of an oral structure that can be used to produce a positive cast of a patient's teeth as a permanent record. The accuracy of the impression affects the accuracy of the cast, and a precise impression is needed in order to create prosthesis with optimal fitting. Minimization of misfit is an important aim in prosthesis science and dental implants. The aim of this study was to evaluate the effects of the materials and techniques used to take an impression on the vertical misfit of implant-supported, screw-retained, three-unit bridges. Materials and Methods: The principal model used was an acrylic block with two ITI implants. A 1.5-mm abutment was attached to fixtures with torque of 25 N.cm. A base-metal framework was built on the abutment in the acrylic block. The abutments of the acrylic model were unscrewed and fixture-level impressions were made. The impression techniques included open/closed-tray techniques and the impression materials were polyether and polyvinyl siloxane. Forty acrylic custom trays were built for each impression. The marginal gap in the framework at three points (buccal, lingual, and distal) was measured using an optical microscope with ×250. Results: It is demonstrated that in all 360 evaluated samples, the mean vertical misfit in polyether samples of molar and premolar teeth was significantly lower than in polyvinyl siloxane (P < 0.001 and P = 0.017, respectively) in all three locations of the molar and lingual premolar examined (buccal, lingual, and distal), the mean vertical misfit of the polyether samples was significantly lower than those of polyvinyl siloxane (P < 0.01). On the other hand, although the mean vertical misfit using the open-tray technique in the molar teeth was significantly lower than with the closed-tray method (P = 0.002), no statistical difference was seen between the open-tray and closed-tray technique in general (P = 0.87). Conclusion: Within the limitations of this study, the following conclusions can be drawn: The impression method had no effect on marginal discrepancy of 3-unit screw retained fixed partial dentures. A higher marginal accuracy was obtained using polyether impression material compared to polyvinyl siloxane.